Inhibitory effect of trans-ferulic acid on proliferation and migration of human lung cancer cells accompanied with increased endogenous reactive oxygen species and β-catenin instability. Issue 1 (December 2016) - Fong, Yao; Tang, Chia-Chun; Hu, Huei-Ting; Fang, Hsin-Yu; Chen, Bing-Hung; Wu, Chang-Yi; Yuan, Shyng-Shiou; Wang, Hui-Min; Chen, Yen-Chun; Teng, Yen-Ni; Chiu, Chien-Chih
Abstract Background Trans -ferulic (FA) acid exhibits antioxidant effects in vitro. However, the underlying mechanism oftrans -FA activity in cellular physiology, especially cancer physiology, remains largely unknown. This study investigated the cellular physiological effects oftrans -FA on the H1299 human lung cancer cell line. Methods The 2, 2-diphenyl-1-picrylhydrazyl assay was used to determine free radical scavenging capability. Assessment of intracellular reactive oxygen species (ROS) was evaluated using oxidized 2ʹ, 7ʹ-dichlorofluorescin diacetate and dihydroethidium staining. Trypan blue exclusion, colony formation, and anchorage-independent growth assays were used to determine cellular proliferation. Annexin V staining assay was used to assess cellular apoptosis by flow cytometry. Wound healing and Boyden's well assays were used to detect the migration and invasion of cells. Gelatin zymography was used to detect matrix metalloproteinase (MMP-2 and MMP-9) activity. Western blotting was used to detect expression levels of various signaling pathway proteins. Results DPPH assay results indicated thattrans -FA exerted potent antioxidant effects. However, trans -FA increased intracellular ROS levels, including hydrogen peroxide and superoxide anion, in H1299 cells.Trans -FA treatment inhibited cellular proliferation and induced moderate apoptotic cell death at the highest concentration used (0.6 mM). Furthermore, trans -FA moderately inhibited the migration of H1299 cells at the concentrations of 0.3 and 0.6 mM and attenuated MMP-2 and MMP-9 activity.Trans -FA caused the phosphorylation of β-catenin, resulting in proteasomal degradation of β-catenin. Conversely, trans -FA treatment increased the expression of pro-apoptotic factor Bax and decreased the expression of pro-survival factor survivin. Conclusion Various concentrations (0.06–0.6 mM) oftrans -FA exert both anti-proliferation and anti-migration effects in the human lung cancer cell line H1299.